MRI of corpus callosum in patients with autism spectrum disorder in Kuantan - Shamsuddin Perisamy, Rajeev; Abd. Aziz, Azian; Mat Zin, Nora; Hasan, Taufiq Hidayat; Abdul Rahim, Mohamad Shahrir (Korean Radiological Society, 2021)
OBjective: To study the integrity of the corpus callosum among autistic children population in Kuantan, Pahang, Malaysia, which is determined by MRI’s diffusion tensor imaging (DTI) parameters, fractional anisotropy (FA) and radial diffusivity (RD). These param- eters represent the direction dependence of water molecules diffusion within the measured tissues. As corpus callosum is saturated with brain white matter tracts, the water molecules diffusion here will be direction dependent. Studies involving foreign populations have shown that there is distortion in the corpus callosum’s DTI parameters in autistic population indicative of microstructural distor- tion. Whether similar findings will be observed in our local autistic population still remains a question. Other gross corpus callosum parameters such as its thickness, length and size are also studied. Materials & Methods: 28 randomly selected autistic children under the International Islamic University Malaysia Medical Centre (IIUMMC), Kuantan follow-up are subjected to MRI scan. Limited MRI sequences including DTI are obtained and analysed. FA, RD, midsagittal thickness at the genu, body and splenium of the corpus callosum as well as its midsagittal length and size are measured. Data are tabulated according to age followed by statistical analysis. Results: A weak negative correlation is found between the age and the FA of the corpus callosum. Other parameters such as the thickness, length and size show weak positive correlation with age. Conclusion: Although the correlation is weak, our study shows that there is evidence of distortion of corpus callosum white matter microstructure in children with autism spectrum disorder in Kuantan, Pahang.